2016
DOI: 10.1088/1751-8113/49/16/165303
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of interacting bosons using the Herman–Kluk semiclassical initial value representation

Abstract: Recent experimental progress in monitoring the dynamics of ultracold gases in optical lattices necessitates a quantitative theoretical description for a significant number of bosons. In the present paper, we investigate if timedependent semiclassical initial value methodology, with propagators expressed as integrals over phase space and using classical trajectories, is suitable to describe interacting bosons, concentrating on a single mode. Despite the nonlinear contribution from the self-interaction, the corr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 33 publications
(58 reference statements)
1
12
0
Order By: Relevance
“…Following the steps learned from the study of quantum interference in mesoscopic systems, we then calculated the Fock-space version of the mesoscopic dynamical echo, and found a universal enhancement of the return probability due to the interplay between interference and interactions. This prediction, successfully confirmed in numerical calculations presented in [5], shows the power of the semiclassical thinking in many-body systems, a road that has been shown to be useful for other set-ups like the 1-site Bose-Hubbard system [44], the WKB approach for the 2-site case of [45][46][47][48][49], bosonic transport in optical lattices [50], connecting soliton-like solutions of discrete nonlinear equations with properties of the quantum spectra [51], investigating spectral statistics of fully chaotic systems [52][53][54][55] and going beyond the classical truncated Wigner method to describe dynamical processes in many-body systems [56]. While the extension of our methods to non-relativistic Fermionic fields on the lattice (partially initiated in [57]) is the subject of work in progress, the ultimate goal of addressing fully fledged quantum fields in the continuum, or equivalently an infinite number of possible single-particle orbitals, will face fundamental aspects of such systems in the presence of interactions 2 like renormalization issues, well beyond the present tools of semiclassical analysis.…”
Section: Resultssupporting
confidence: 60%
“…Following the steps learned from the study of quantum interference in mesoscopic systems, we then calculated the Fock-space version of the mesoscopic dynamical echo, and found a universal enhancement of the return probability due to the interplay between interference and interactions. This prediction, successfully confirmed in numerical calculations presented in [5], shows the power of the semiclassical thinking in many-body systems, a road that has been shown to be useful for other set-ups like the 1-site Bose-Hubbard system [44], the WKB approach for the 2-site case of [45][46][47][48][49], bosonic transport in optical lattices [50], connecting soliton-like solutions of discrete nonlinear equations with properties of the quantum spectra [51], investigating spectral statistics of fully chaotic systems [52][53][54][55] and going beyond the classical truncated Wigner method to describe dynamical processes in many-body systems [56]. While the extension of our methods to non-relativistic Fermionic fields on the lattice (partially initiated in [57]) is the subject of work in progress, the ultimate goal of addressing fully fledged quantum fields in the continuum, or equivalently an infinite number of possible single-particle orbitals, will face fundamental aspects of such systems in the presence of interactions 2 like renormalization issues, well beyond the present tools of semiclassical analysis.…”
Section: Resultssupporting
confidence: 60%
“…We also wish to consider condensates in multi-well traps, such as a multi-site ver-sion of the Bose-Hubbard model studied in Ref. [61], and other interesting systems that have previously been studied by ML-MCTDHB [45][46][47][48][49][50][51][52].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the use of coherent states in CCSB and their relation to the creation and annihilation operators of second quantisation, together with the fact that systems with a large number of particles tend towards classical behaviour and arXiv:1811.06293v3 [quant-ph] 28 Jun 2019 the basis in CCSB is guided by classical-like trajectories, suggest that the method will be particularly suited to such systems. Indeed, recent semiclassical coherent state work with the Herman-Kluk method on indistinguishable bosons demonstrates this hypothesis [60,61]. CCSB is fully quantum however, as with standard CCS, and it has previously been shown that a local quadratic approximation of the Hamiltonian into the CCS equations yields the coherent state matrix of the Herman-Kluk propagator [62].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…This idea can be transferred to other semiclassically-treated problems, e.g. in the context of molecular spectroscopy [47,59,60] or interacting bosons [61], with the advantage of a clearer view on physical processes compared to previously used initial-value representations.…”
mentioning
confidence: 99%